Morphological and molecular characterisations of \(Scutellonema brachyurum\) (Steiner, 1938) Andrassy, 1958 from the western highlands, Vietnam - Phap Trinh, Quang; Nguyen, Thi Duyen; Linh Le, Thi Mai; Tien Nguyen, Huu (Academia Journal of Biology, 2022)
The genus Scutellonema consists of about 50 species that are phytophagous (ecto- and partially endo-parasites). Among species of the genus Scutellonema, Scutellonema brachyurum was reported to be one of the three most damaging ones, causing serious symptoms to numerous host plants worldwide. In the past, Scutellonema species have been described using morphological and morphometric characterizations, however, cryptic species have been proven to exist in the genus. Therefore, molecular data is clearly needed in identifying Scutellonema species to ensure correct outcomes. In this study, we provide morphological and molecular characterizations of S. brachyurum recovered from the rhizosphere of Vietnamese ginseng for the first time. Morphological comparison and PCA analysis indicated that our nematode population is closer to S. brachyurum type B, however, molecular data of D2-D3 of 28S rRNA region indicates that the Vietnamese population of S. brachyurum belongs to type A. Our study also provides the 18S rRNA sequence of S. brachyurum for the first time in GenBank (only 18S sequences of Scutellonema bradys are available in the genus Scutellonema before this study). Phylogenetic trees based on 18S and D2-D3 sequences are also provided for a better understanding of the relationships between Scutellonema species. Besides, this species was found in association with tuber rot symptom of the host plant, implying potential pathogenicity, and thus, more attention needs to be paid to better understand this pest.